AL-MANHAJ AL-NABAWI FĪ AL-TA’ĀMUL MA’A GHAYR AL-MUSLIM - Islam Hasan Tazaza (Universitas Islam Negeri Ar-Raniry, 2021)
The problem of dealing with different parties' affairs is one of the most critical problems that the state and government are trying to solve. Religious and intellectual differences are one of the most important reasons for the emergence of conflicts in society. Factual conditions show how the state experiences war conflicts between people of different religions and ideas. With its fair statutory provisions, Islam has provided the right solution to overcome the manifestations of conflict and disputes between Muslims and those of different religions and beliefs. Using an analytical method based on gathering information related to the topic, followed by an interpretation, criticism, and analysis, this study clarifies the concept of non-Muslims in Islam, its parts, and the differences between these parts, including the essential aspect of which is the Prophet Muhammad's guidance in dealing with non-Muslims. The research found that the difference for non-Muslims is a set of rights over Muslims, the state, and the people. When non-Muslims exercise these rights, they are entitled to full protection and security for themselves, their property, and their children. They also have the freedom to worship and believe according to their religion. In this context, the Islamic State and Muslims must guarantee this freedom to them.